2018
DOI: 10.1371/journal.pone.0190320
|View full text |Cite
|
Sign up to set email alerts
|

Does the leading pharmaceutical reform in China really solve the issue of overly expensive healthcare services? Evidence from an empirical study

Abstract: BackgroundHealthcare system reform of Sanming city has become a leading healthcare reform model in China. It has developed a rigorous pharmaceutical reform consisted of the Zero Mark-up Drug Policy and the Centralized Procurement of Medicine Policy to bring down drug expenses and total health expenditures. However, despite the credit and much attention have been given to Sanming’s pharmaceutical reform, its impact still remains unclear. Therefore, the purpose of this study was to explore the impact of the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 10 publications
0
49
0
Order By: Relevance
“…use, unnecessary drug use is serious in China (8)(9)(10). A close interest relationship between drug sales and prescriptions made unnecessary prescriptions and drug rebates prevail in the long term (11). Physicians in China tend to rely heavily on drug revenue due to the existence of profit margins on drugs (12).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…use, unnecessary drug use is serious in China (8)(9)(10). A close interest relationship between drug sales and prescriptions made unnecessary prescriptions and drug rebates prevail in the long term (11). Physicians in China tend to rely heavily on drug revenue due to the existence of profit margins on drugs (12).…”
Section: Original Articlementioning
confidence: 99%
“…There are two typical mark-up drug policies, one is Fixed Percent Mark-up Drug (FPM) policy, which allows drugs to be sold on fixed mark-up percent based on the purchase price; the other is Zero Mark-up Drug (ZMD) policy, which requires all public hospitals to prescribe drugs at purchase price without including a mark-up (23). Previous studies mostly presented positive effects on healthcare expenditures shortly after implementing ZMD policy, but showed mixed results regarding long-term effects (11,14,24). Regarding FPM policy, hospitals were found to show more preference for expensive drugs, which led to increasing healthcare expenditures and high drug revenue proportion in both outpatient and inpatient healthcare revenue (9,25).…”
Section: Original Articlementioning
confidence: 99%
“…We excluded 25 records that did not meet our inclusion criteria. Nine studies (included time series study, retrospective cohort study, and quasi-experimental study) were included in this systematic review [1][2][3][4][6][7][8][9][10]. The characteristics of the included studies are summarized in Table 3.…”
Section: Characteristics Of the Included Trialsmentioning
confidence: 99%
“…Fu et al (2018) showed that a rise in expenditures for medical services and no changes in total health expenditures [8]. In addition, He et al (2018) showed the results that pharmaceutical reform could not reduce total health expenditure in long term [3]. There was a statistical significantly positive correlation between the rate of services compensation and the proportion of medical service revenue [1].…”
Section: Total Expensesmentioning
confidence: 99%
See 1 more Smart Citation